Evaluating the Protective Effect of Ailanthus altissima (Mill.) Swingle in a Rat Model of Acetic Acid-Induced Ulcerative Colitis - Mohammad Mehdi Gravandi; Seyede Zahra Hosseini; Seyede Darya Alavi; Seyed Mohammad Reza Jafari; Mohsen Zhaleh; Mohammad Hossein Farzaei (Tehran University of Medical Sciences, 2023)
Inflammatory bowel disease (IBD) has two subtypes called ulcerative colitis (UC) and Crohn's disease (CD). They have the same tissue damage processes; however, differ in the initial procedures and immune regulatory aberrations. Tumor necrosis factor-alpha (TNF-α) appears to have an important function and a key pathogenic role in CD and UC. In this paper, we evaluated the protective impact of the extract of Ailanthus altissima (Mill.) Swingle (tree of heaven), Simaroubaceae, in acetic acid-induced UC. Ferric-reducing capacity of plant extract, total phenols, and total flavonoid contents were measured in A. altissima ethanolic extract. Thirty male rats were randomly divided into six groups including control, normal, mesalazine 300 mg/kg (positive control) and 3 treatment groups with doses of 50, 100, and 200 mg/kg for 7 days. Except for the normal group, all animals received 2 mL of 4% acetic acid infusion into the large intestine. Upon 48 h after the last gavage, the animals were euthanized. Acetic acid intracolonic administration resulted in a severe acute inflammation in the colonic tissue, which was improved by A. altissima extract at all examined doses in both microscopic and macroscopic aspects. In comparison to the control, TNF-α was considerably lower in the mesalazine and 200 mg/kg A. altissima extract groups. Conclusively, the valuable effects of the extract in the treatment of UC were confirmed by TNF-α levels, histological data, and macroscopic observations, especially at 200 mg/kg dosage. Future studies are recommended to further clarify the action mechanisms of this plant.